If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3l + 4 + l = 13 + e Reorder the terms: 4 + 3l + l = 13 + e Combine like terms: 3l + l = 4l 4 + 4l = 13 + e Solving 4 + 4l = 13 + e Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4l = 13 + -4 + e Combine like terms: 4 + -4 = 0 0 + 4l = 13 + -4 + e 4l = 13 + -4 + e Combine like terms: 13 + -4 = 9 4l = 9 + e Divide each side by '4'. l = 2.25 + 0.25e Simplifying l = 2.25 + 0.25e
| 2a+8b+10a-6b= | | 8x+3=12+3x | | -(6y+5)-(-5y-7)=-3 | | 2x-44=2x | | .25r-0.25+0.25r=.5-0.25r | | ln(x)+ln(x-2)=5 | | h=-16t^2+112t+128 | | 5n-2=-2 | | ln(x)+ln(-2)=5 | | 5*n-2=-2 | | m+4=-16 | | -1+6x-4x=-1 | | -1+-6x-4x=-1 | | 2(x(x))=16 | | 5(-4q+3)=2q+3 | | 4(4x-2)=2(8x+4) | | 18+21.30-(-15)= | | 8=4-2y | | 3n+(-6)=-15 | | 36y^8+4y^4= | | 4r-7r=27 | | 6+2s-4=8s+9-5s | | 4X+2=14whatisX | | (x-9)(x-4)=0 | | 2(x-18)+6(x+2)=x+4 | | 3*5+3*6= | | 3*(5+6)= | | 10x-8x-3x=0 | | x^2+21x-38=0 | | 3x(5+6)= | | 8s+3s=44 | | -32+9=-14-11x |